Análise da técnica de corrida por meio de variáveis biomecânicas em corredores de rua de diferentes faixas etárias - Rodrigues, Mario Eduardo Santos (2019)
When we started running, we went through a very rapid performance improvement process in the first months of training. Over time, we have reached a level that no longer seems to be possible to improve. Sometimes we cannot even maintain the performance achieved. What happens to our body? Is it possible to train to maintain or even improve our performance with aging? Some studies have been done to analyze aspects of the performance change of running athletes with aging. Basically these researches are restricted to two groups of variables: physiological and biomechanical. The first group analyzes the physiological behavior of the human body and the second group analyzes the kinematic and dynamic aspects of running. In this research we investigated only the biomechanical variables in their angular and spatiotemporal aspects. We analyzed these variables in groups of runners of different age groups in order to point out which of the biomechanical parameters analyzed change over time. Over time musculoskeletal degenerative processes and changes, loss of lower limb joint mobility, and progressive weakness in muscles and bones can lead to reduced ground reaction force during the driving phase of the race, thus raising the following question: change in biomechanical aspects of running with aging? One hundred male runners, aged 19 to 72 years old, who had been running for over a year, participated in this research. The volunteers were divided into 6 groups aged 9 years and 9 years and they were evaluated at 4 different times. Bioimpedance body composition analyzes were performed, an analysis of angular variables using a 3D motion capture system, a sequence of three vertical jumps on a force platform and a 2400 meter run on the track for performance analysis. The results showed a change in the biomechanics of running with aging. The ankle angle does not change with our aging, but the internal angle of the knee tends to be less flexed while the hip angle tends to increase its maximum amplitude. Vertical displacement decreases with increasing age. Older runners run “flexing” while younger runners show a higher flight phase. Older runners tend to shorten stride length and increase stride frequency.